1986
DOI: 10.1016/0166-4328(86)90043-4
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between response stereotypy and memory strategies on the eight-arm radial maze

Abstract: !Three groups of water-deprived rats collected water from the ends of the 8 arms of an 8-arm radial maze. Sighted subjects, and subjects blinded either with or without pre-enucleation experience on the radial maze, all retrieved the water efficiently. Most of the subjects exhibited the same response stereotypy, regularly choosing 8 adjacent arms of the maze, then stopping in the center of the maze. The strategies underlying this performance were analyzed by interrupting trials and rotating the maze 180° after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 49 publications
2
26
1
2
Order By: Relevance
“…Thus, the bias to visit adjacent arms demonstrated by the ratsin the short-arm condition persisted even when it resulted in a substantial number of errors. This is quite different from the results of previously reported experiments in whichrats continued to exhibithigh levels of choice accuracy when stereotypic response patterns were disrupted (Dale& Innis, 1986;Olton et al, 1977).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Thus, the bias to visit adjacent arms demonstrated by the ratsin the short-arm condition persisted even when it resulted in a substantial number of errors. This is quite different from the results of previously reported experiments in whichrats continued to exhibithigh levels of choice accuracy when stereotypic response patterns were disrupted (Dale& Innis, 1986;Olton et al, 1977).…”
Section: Resultscontrasting
confidence: 99%
“…In agreement witha numberof previous findings (e.g., Brown & Cook, 1986;Dale & Innis, 1986;Foreman, 1985;Olton et al, 1977), the rats in the present experimentexhibited somedegree of stereotypy in their choice behavior. The majority of choices made in both groups were to arms either adjacent to, or separated by a single arm from, the previous choice.…”
Section: Blocks Of 20 Sessions Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A more complex but flexible system is the use of a cognitive map in which the goal is defined by its spatial relation to a number of landmarks (O'Keefe and Nadel 1978), thus the loss of a single landmark does not alter success; however, the loss of multiple cues in a disrupted habitat could result in an animal failing to return successfully to a resource. This is considered a highly efficient navigational mechanism that allows an animal to cope with some environmental change; however, it imposes a high burden on memory load (Dale and Innis 1986). Alternatively, animals can navigate using a response-based strategy in which a goal is reached by performing a specific sequence of responses (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies reported that successive choices were made almost randomly, and neither response chains nor general algorithms were necessary for accurate arm choice (Olton, 1978, for a review). However, subsequent studies found evidence of the strategy of response chains, such as adjacent-arm choices (Dale & Innis, 1986;Yoerg & Kamil, 1982). For example, Roberts and Dale (1981) showed that percentage of the adjacent-arm choices increased to over 90% at the end of training.…”
mentioning
confidence: 99%